RETRACTED: Multiattribute decision making based on nonlinear programming methodology, score function of interval-valued intuitionistic fuzzy values, and the dispersion degree of score values - Chen, Shyi-Ming; Huang, Shao-En (Information sciences, 2023)
This article has been retracted: please see Elsevier Policy on Article Withdrawal (https://www.elsevier.com/locate/withdrawalpolicy). This article has been retracted at the request of an independent subject matter expert appointed by the journal. Post-publication, the journal became aware of significant similarities between this article and the following six publications:·Multiattribute Decision Making Based on Nonlinear Programming Methodology, Novel Score Function of Interval-Valued Intuitionistic Fuzzy Values, and Standard Deviations of the Score Values in the Score Matrix, Shyi-Ming Chen, An-Yuan Liu, Information Sciences, Volume 646, October 2023, 119381, https://doi.org/10.1016/j.ins.2023.119381·Multiattribute Decision Making Method Based on Nonlinear Programming Model, Cosine Similarity Measure, and Novel Score Function of Interval-Valued Intuitionistic Fuzzy Values, Shyi-Ming Chen, Mei-Ren Ke, Information Sciences, Volume 64, October 2023, 119370, https://doi.org/10.1016/j.ins.2023.119370·Multiple Attribute Decision Making Based on MAIRCA, Standard Deviation-Based Method, and Pythagorean Fuzzy Sets, Pratibha Rani, Shyi-Ming Chen, Arunodaya Raj Mishra, Information Sciences, Volume 644, October 2023, 119274, https://doi.org/10.1016/j.ins.2023.119274·Multiattribute Decision Making Based on Nonlinear Programming Model, the Gini Coefficient, and Novel Score Function of Interval-Valued Intuitionistic Fuzzy Values, Shyi-Ming Chen, Hao-Chen Ma, Information Sciences, Volume 647, November 2023, 119317, https://doi.org/10.1016/j.ins.2023.119317·Multiple Attribute Decision Making Based on Novel Nonlinear Programming Model, the Distance Between Score Values, and Novel Score Function of Interval-Valued Intuitionistic Fuzzy Values, Shyi-Ming Chen, Guan-Lin Lu, Information Sciences, Volume 645, October 2023, 119369, https://doi.org/10.1016/j.ins.2023.119369·Multiattribute Decision Making Based on Nonlinear Programming Methodology, the Euclidean Distance between IVIFVs, and New Score Function of IVIFVs, Shyi-Ming Chen, Pei-Hsun Kao, Information Sciences, Volume 646, October 2023, 119403, https://doi.org/10.1016/j.ins.2023.119403 An independent expert was asked to assess the alleged similarities between the articles and found that all seven articles use similar data sets, specifically focusing on interval-valued intuitionistic fuzzy sets. They utilize five score functions, which are embedded versions of each other, neither one offering a significant advantage over the other, and the possible solution sets they provide in the NLP are identical. The examples used across these papers are highly similar. The authors utilize these score functions to embed fuzzy NLP problems into real NLP problems, without considering the correspondence of the solutions. While this is a valid technique, the identical solution sets across papers, with only minor differences in the objective functions, show a lack of originality between the articles. In addition, an investigation found irregularities in the reference selection process, with 20 references added during revision either as new sources or replacing previously referenced work, while only six of these were highlighted for the editors and reviewers who were assessing the revised manuscripts. Thirteen of the 20 references are for articles published by one journal. The journal requested the authors to comment on the similarities between the articles listed above and the reference selection irregularities, but the authors' explanation did not satisfactorily address the independent expert's concerns. Consequently, the expert no longer has confidence in this article and has decided to retract it. The scientific community takes a very strong view on this matter and apologies are offered to readers of the journal that this was not detected during the submission process. The authors have not responded to this retraction.